A lateralized model of the pain-depression dyad. (August 2021) - Maallo, Anne Margarette S.; Moulton, Eric A.; Sieberg, Christine B.; Giddon, Donald B.; Borsook, David; Holmes, Scott A.
Highlights: Lateralized non-organic pain is equally probable on either side of the body. Left hemibody pain is accompanied by greater psychological distress. Characteristic combinations of symptoms lead to comorbid pain and depression. Abstract: Chronic pain and depression are two frequently co-occurring and debilitating conditions. Even though the former is treated as a physical affliction, and the latter as a mental illness, both disorders closely share neural substrates. Here, we review the association of pain with depression, especially when symptoms are lateralized on either side of the body. We also explore the overlapping regions in the forebrain implicated in these conditions. Finally, we synthesize these findings into a model, which addresses gaps in our understanding of comorbid pain and depression. Our lateralized pain-depression dyad model suggests that individuals diagnosed with depression should be closely monitored for pain symptoms in the left hemibody. Conversely, for patients in pain, with the exception of acute pain with a known source, referrals in today's pain centers for psychological evaluation should be part of standard practice, within the framework of an interdisciplinary approach to pain treatment.